SOUTH AFRICAN MOTIVATIONS FOR SUPPORTING INTERNATIONAL HUMANITARIAN INTERVENTIONS BY NON-GOVERNMENTAL ORGANIZATIONS - Miller, Stephen (My University, 2014)
Humanitarian aid delivered during times of emergency is a critical resource not only for responding to immediate needs, but also for helping affected communities to build resilience and to combat poverty over the longer term. However, recent reductions in official humanitarian aid by many western governments have resulted in unmet financing needs being at their worst in over a decade. With limited government resources available, International Non-Governmental Organizations (INGOs) have come to rely increasingly upon private voluntary contributions when responding to complex humanitarian emergencies. Existing research into the social giving habits of South African citizens suggests that substantial private resources for international humanitarian work may be available for INGOs in this country, despite academic claims to the contrary. However, minimal research has thus far been conducted into the propensity for South Africans to donate to international causes. This research paper is a preliminary investigation into the increasing internationalisation of charitable giving in South Africa. The primary data source is the self-reported motivations of South African citizens who regularly give unrestricted financial support to Médecins Sans Frontières / Doctors Without Borders (MSF) for humanitarian work that is conducted outside of South Africa’s borders. The paper’s findings are further based on quantitative data from an on-site poll and an extensive literature review. The purpose is to better understand the giving behaviour of current donors to international causes, so as to inform further research into the likelihood for South Africa to become a major source of private funding for global humanitarian assistance. The research paper concludes that that there is great potential for INGOs to solicit financial support for international causes from South African donors.
MM (P&DM) thesis
Keywords: Humanitarian intervention; Humanitarian aid